STAGED EMBOLIZATION OF A DOUBLE ARTERIOVENOUS MALFORMATION IN ADULTS - AHMED, A; BAWNA, .; FARID, MI; ABURABEE, AI; AHMED, SN; AHMAD, I; KHAN, AA (Biological and Clinical Sciences Research Journal, 2024)
Arteriovenous malformations (AVMs) are rare vascular anomalies where abnormal connections form between arteries and veins, bypassing the capillary network that typically regulates blood flow. Objective: The study’s main objective is to find the staged embolization of a double arteriovenous malformation in adults. Methods: This prospective observational study was conducted at Fatima Jinnah Medical University, Lahore, from January 2022 to January 2023. A total of 125 adult patients diagnosed with double AVMs were included in the study. Patients aged > 18 years and with confirmed double AVMs (detected on imaging), no previous AVM treatment, and who were eligible for embolization based on clinical and imaging findings were included in the study. Results: Data were collected from 125 patients with a mean age of 45.2 ± 5.46 years. The gender distribution was 56% male (70 patients) and 44% female (55 patients). The average size of the arteriovenous malformations (AVMs) was 4.8 cm, ranging from 2.5 to 6.5 cm. According to the Spetzler-Martin grading system, most patients were classified as Grade III (44%), followed by Grade II and IV (20% each), with 8% in both Grade I and V. The embolization treatment for the patients was conducted in multiple stages, with 40% undergoing 3 stages, 28% undergoing 4 stages, and 24% undergoing 2 stages. A smaller group (8%) required 5 stages of embolization. Onyx was the most commonly used embolic agent (64%), followed by n-butyl cyanoacrylate (28%) and coils (8%). The average interval between stages was 5.2 weeks. Conclusion: It is concluded that staged embolization is an effective and safe approach for managing double arteriovenous malformations (AVMs) in adults, offering high rates of occlusion while minimizing the risk of complications.